Spiritual Dimension in Art Therapy - Beyza Kırca (Spiritual Psychology and Counseling)
Spiritually-oriented art therapy interventions are based on a holistic, therapeutic approach that aims to enable people who are in fragmented states to achieve integrity, unity, harmony, and balance by taking all the mental, emotional, physical, and spiritual dimensions of human nature into account using the medium of art and its creative processes. Art is considered intrinsically spiritual by many artists and art therapists, and the history of art and its relationship to treatment is as old as human history; however, open consideration of the spiritual dimension in therapeutic settings, particularly in art therapy interventions, is relatively new. Reviewing the emergence of spiritually-oriented art therapy interventions and their mechanisms of change is considered useful for seeing how they enable holistic transformation. These mechanisms have been determined as self-realization and understanding, transcendence, meaning-making and searching for a purpose, and achieving integrity through the holistic wellbeing approach.